Tratamiento quirúrgico de los cavernomas del tronco encefálico - Viñas, Federico C.; Gordon, Vickie; Díaz, Fernando G. (Revista Argentina de Neurocirugía, 2021)
Brain stem cavernomas can bleed repeatedly causing significative neurological sequelae in spite that their treatment is controversial, most authors recommend surgery when cavernomas bleed, have a progressive defieit and/ or are easy to approach. The role of radiosurgery is not clear and some authors think that is contraindicated.